Sting of the scorpion the inside story of the Long Range Desert Group - Morgan, Mike 1953- (Sutton, 2000)
The Long Range Desert Group was Britain's original special force operating in the Western Desert, long before the SAS were created. This is the inside story of the LRDG raiders of World War II, written from the unpublished records of the force.